Snowboarding injuries - a focus on the lower extremties - Krüger, A.; Michel, F. I.; Niemann, S.; Edelmann-Nusser, J. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Lower extremity injuries account for one third of all injuries in recreational snowboarding. Little is known regarding preventive measures for lower extremity injuries in snowboarding. To overcome this, information about the injured anatomical structures is needed. So far, few studies have looked at injured anatomical structures in detail (e.g. Ishimaru et al., 2011). However, an overall as well as a detailed description of injured anatomical structures is still missing. Therefore, the purpose of this epidemiological study is to analyse injured anatomical structures within the lower extremities in snowboarding. Based on that, links to injury mechanisms as well as to the development of preventive measures could be drawn.